The use of digital tools in sustainability management systems (Research, Society and Development, 2023)
The characteristic of Industry 4.0 is by use of digital tools (HD) to make production operations more effective and thus support companies in caring for the environment. In management systems, one of the problems it addresses is sustainability through the ISO 14000 standard, which provides guidelines to follow this purpose. In this research, conducted within the National Polytechnic Institute, the objective was to establish a model that relates the digital tools as technological support for an information safe word and operation of a Sustainability Management System (SGS), if the effective management of HDs makes the SGS more efficient. A regular correlation was determined between both variables (0.59) and, in turn, high correlations between the dimensions of these variables that we represent in a model and propose actions to improve the use of the HDs and obtain better results in the SGS. The objective was to establish a model of digital tools related to the Sustainability Management System (SGS).